Ultrasounds in gas media: generation, transmission, applications (review paper) - GUDRA, Tadeusz (Archives of Acoustics, 2008)
The focus of this work is on some fundamental issues concerning ultrasonic wave propagation in gas media. First, a short characterization of the gas medium and matters related to transmission of ultrasonic waves in stationary and non-stationary media were presented. Additionally, the study presents an aeroacoustic range equation which is a basis of the development of a computer model of an ultrasonic link. Next, attention turns to matters related to generation of ultrasonic waves in gas media and problems regarding matching high acoustic impedance of transducers and low acoustic impedance of gases. Finally, examples of industrial use of ultrasounds were given and possible future applications in non-contact measurement systems were suggested.